2021
DOI: 10.3390/ani11010084
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Synbiotics and Vitamins at Birth Affects Piglet Microbiota before Weaning and Modifies Post-Weaning Performance

Abstract: Early-life microbial colonization is an important driver for the development and maturation of the gut. The present study aimed to determine whether a single-dose supplement given only at birth would improve piglet performance and modify their fecal microbiota during the suckling and post-weaning periods. At birth, piglets from eight litters received a supplement (SUP+) while piglets from six other litters received water (SUP−). All piglets were monitored until two weeks post-weaning, and fecal samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In last, synbiotics are defined as a mixture comprising live microorganisms (probiotics) and substrate(s) (prebiotics) selectively utilized by host microorganisms that confer a health benefit on the host ( 79 ). According to Girard and colleagues, this combination improves the survival rate and favors the growth and activity of beneficial microorganisms in the gut of the piglets ( 51 ). Among the prebiotics and probiotics evaluated for the control of ETEC colonization in pigs, inulin and Lactobacillus plantarum are the ones that have been more systematically assessed, either individually or in combination (see Table 1 ).…”
Section: Alternative Strategies To Current Therapies For Pwd Controlmentioning
confidence: 99%
“…In last, synbiotics are defined as a mixture comprising live microorganisms (probiotics) and substrate(s) (prebiotics) selectively utilized by host microorganisms that confer a health benefit on the host ( 79 ). According to Girard and colleagues, this combination improves the survival rate and favors the growth and activity of beneficial microorganisms in the gut of the piglets ( 51 ). Among the prebiotics and probiotics evaluated for the control of ETEC colonization in pigs, inulin and Lactobacillus plantarum are the ones that have been more systematically assessed, either individually or in combination (see Table 1 ).…”
Section: Alternative Strategies To Current Therapies For Pwd Controlmentioning
confidence: 99%
“…Previous studies have demonstrated that probiotics improved the reproductive performance of sows and the growth performance of neonatal piglets by improving intestinal microbiota ( Hayakawa et al, 2016 ). Moreover, synbiotics may stimulate the growth of beneficial microbiota, and enhance the production of beneficial bacterial metabolites like short-chain fatty acids (SCFAs) in sows, while decreasing the production of deleterious metabolites, such effects being possibly associated with improved growth performance and gut microbiota balance in piglets ( Śliżewska and Chlebicz, 2019 ; Girard et al, 2021 ). Furthermore, the effects of dietary probiotics and synbiotics may mainly target the cecum and colon of pigs, where an abundant and diverse microbial population is harbored ( Liao and Nyachoti, 2017 ).…”
Section: Introductionmentioning
confidence: 99%